PENANAMAN POHON MAHONI UNTUK PENGHIJAUAN DI DESA SUKAHARJA CIOMAS - Hasni Riyas Alfina; Syaiful Syaiful (Lembaga Penelitian dan Pengabdian kepada Masyarakat UIKA Bogor, 2024)
Trees are plants with wooden trunks with a diameter of 10 cm or more when measured at a height of 1.5 meters above ground level. Trees can also be interpreted as a habitus or plant structure with the ability to photosynthesis so that it can absorb carbon dioxide and produce oxygen. Planting activities include species selection, field preparation, installation of stakes, making planting holes, transporting seeds, planting, replanting as well as work inspection and evaluation of planting. Planting activities have several purposes, including routine planting, enrichment planting, reforestation or greening as well as conservation purposes. Apart from that, planting also aims to obtain healthy stands and have sufficient supplies of plants in the future. This program is implemented using the extension method and is directly applied in the field by inviting RT and several local residents to carry out mahogany tree planting activities in Sukaharja Village. Ciomas sub-district. Greening is an important activity that must be implemented conceptually in dealing with the environmental crisis. It is so important that it has become a national program implemented throughout Indonesia.